Reliability and Validity of the Adapted Nepali Version of the AO Spine Patient Reported Outcome Spine Trauma - Dhakal, Gaurav Raj; Sadiqi, Said; Dhakal, Raju; Dhungana, Siddhartha; Yadav, Pravin Kumar; Shah, Gyanendra; Paudel, Santosh; Bijukachhe, Binod; Yadav, Abhay; Oner, F.Cumhur (Journal of Nepal Health Research Council, 2022)
Background: The AO Spine Patient Reported Outcome Spine Trauma has been validated in English and Dutch language, however, there is an absence of a translated and validated version in Nepali language. The purpose of this study was to translate the AO Spine Patient Reported Outcome Spine Trauma into Nepali and adapt cross-culturally as outlined by established guidelines, as well as test its psychometric properties among Nepali speaking spine trauma patients. Methods: Patients were recruited from two Nepali centers as a cross-sectional multicenter validation study. The English version of AO Spine Patient Reported Outcome Spine Trauma was translated and cross-culturally adapted into Nepali language following international guidelines. Next to AO Spine Patient Reported Outcome Spine Trauma also the EQ-5D-3L was filled out by the patients for concurrent validity. Descriptive statistics were used to analyze the patient characteristics. Assessment of measurement properties included content validity (floor and ceiling effects), internal consistency (Cronbach’s ? and item total-correlation coefficients) and test-retest reliability by the Bland-Altman plot and Intraclass Correlation Coefficients. Spearman correlation tests were performed within the items and in correlation to EQ-5D-3L. Results: Sixty two spine trauma patients completed the instrument with a mean time of 6.8 minutes. The translated version showed good content validity with no floor and ceiling effects. The internal consistency was excellent with a Cronbach’s ? of 0.95. The Spearman correlations within the AO Spine Patient Reported Outcome Spine Trauma items were 0.07 – 0.65 and the test-retest analysis showed excellent results with an Intraclass Correlation Coefficients value of 0.95 (CI 0.93 – 0.97). Inverse correlation was observed between Nepali AO Spine PROST with EQ-5D-3L components. Conclusions: The Nepali version of AO Spine Patient Reported Outcome Spine Trauma demonstrated excellent validity and reliability results for measuring patient-reported outcomes of spine trauma patients. Keywords: AO spine PROST: Nepali; translation; validation.